A Game-Based Online Tool to Measure Cognitive Functions in Students - Valeska Berg (Serious Games Society, 2021)
Cognitive assessments can be expensive, lengthy and fatiguing for students and are often conducted in an artificial clinical context. In an effort to make the assessments more fun, researchers have started to introduce game elements to traditional cognitive tasks and training. This comes with a number of challenges. The main challenge is to develop an engaging tool that at the same time reliably assesses cognitive constructs in students. To address these challenges, this research aims to improve cognitive assessment with a new game-based assessment app that has been designed and developed in collaboration with researchers, teachers, students, and software engineers based on established cognitive theories, and subsequently validated through iterative testing in real world settings. The iterative development process is based on design-based research and includes cycles of design explorations, testing, analyses, redesign, and evaluation with students in authentic educational settings. The knowledge gained from the iterative process of designing a valid cognitive function app can inform other researchers who are aiming to develop cognitive assessment tools in an educational context.